Isolation, Characterization and Quantity Determination of Aristolochic Acids, Toxic Compounds in Aristolochia bracteolata L. - Abdelgadir A. Abdelgadir; Elhadi M. Ahmed; Mahgoub Sharif Eltohami (SAGE Publishing, 2011)
Background Aristolochic Acids (AAs) are major components of plants in Aristolochia and have been found to be nephrotoxic, carcinogenic and mutagenic. Herein reported are the isolation, identification and quantity determination methods of Aristolochic Acid-I (AA-I) and Aristolochic Acid-II (AA-II) toxic compounds of Aristolochia bracteolata indigenous to Central Sudan and medicinally used in diverse biological functions including analgesic and diuretic effects, treatment of tumors, malaria and/or fevers. Methods and results AAs mixture was extracted with methanol from the defatted material of Aristolochia bracteolata whole plant at room temperature and was isolated from the aqueous methanol extract by chloroform. Moreover, Silica-gel column chromatography and Preparative Thin Layer Chromatography (PTLC) using chloroform/methanol gradient mixtures were used to isolate AAs mixtures as a yellow crystalline solid. A preliminary detection of AAs was made by Thin Layer Chromatography (silica-gel, chloroform: methanol (6:1)). The Rf value of the acids mixture was 0.43-0.46. The presence of AAs in plant sample was confirmed by High Performance Liquid Chromatography/Ultraviolet (HPLC/UV) analysis using 1% acetic acid and methanol (40:60) as mobile phase and maximum absorption wave length of 250 nm. Quantitative determination of AA-II (49.03 g/kg) and AA-I (12.98 g/kg) was also achieved by HPLC/UV. Recommendation It is recommended that the use of Aristolochia bracteolata as a medicinal plant should be extremely limited or strictly prohibited. The chromatograms obtained in this study can serve as fingerprints to identify AAs in plant samples.